LATIN AMERICAN DIRECTION OF UKRAINE'S FOREIGN POLICY UNDER MARTIAL LAW (Вісник: Міжнародні відносини, 2025)
B a c k g r o u n d . For Ukraine, which is fighting against Russian aggression, it is strategically important to develop cooperation with LatinAmerican countries and enlist their support. In this context, the development of bilateral and multilateral relations with the region should be studiedin light of international political and security changes and modern integration processes, considering the foreign policy initiatives of leading statesand the activities of international organizations.M e t h o d s . Systemic and dialectical methods allowed us to consider the problem in detail and perceive relations between Ukraine and LatinAmerica as a dynamic and changing phenomenon. The logical method provided the basis for a detailed analysis of the subject of research and theformulation of the author's generalizations.R e s u l t s . The article analyzes the key directions of Ukraine's foreign policy in relations with Latin American countries under martial law. It isemphasized that the Russian war against Ukraine had a significant impact on relations, as well as the strengthening of the role of the countries of theLatin American region in international processes that updated the world agenda. It is established that the current level of interaction between Ukraineand Latin American countries remains insufficiently effective, primarily due to the low level of mutual information about events in both regions. Themain stages and tools of cooperation are outlined, mainly bilateral initiatives and interaction through international organizations, which allow for amore effective multilateral dialogue. Such dialogue covers numerous areas of activity, considers partners' multifaceted interests and actively usesmechanisms of soft influence. It is noted that joint projects and exchange of experience contribute to developing scientific potential and introducingmodern technologies.C o n c l u s i o n s . Based on the study of interregional meetings, summits and negotiation processes, it is confirmed that trust and mutualunderstanding can be achieved only by finding optimal cooperation mechanisms between Ukraine and Latin American countries. Rational use of thepotential of bilateral and multilateral interaction will contribute to strengthening Ukraine's position in the international arena.